Paying for Plasma: Commodification, Exploitation, and Canada's Plasma Shortage - Panitch, Vida; Horne, Lendell Chad (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
A private, for-profit company has recently opened a pair of plasma donation centres in Canada, at which donors can be compensated up to $50 for their plasma. This has sparked a nation-wide debate around the ethics of paying plasma donors. Our aim in this paper is to shift the terms of the current debate away from the question of whether plasma donors should be paid and toward the question of who should be paying them. We consider arguments against paying plasma donors grounded in concerns about exploitation, commodification, and the introduction of a profit motive. We find them all to be normatively inconclusive, but also overbroad in light of Canada’s persistent reliance on plasma from paid donors in the United States. While we believe that there are good reasons to oppose allowing a private company to profit from Canada’s blood supply, these concerns can be addressed if payment is dispensed instead by a public, not-for-profit agency. In short, we reject profiting from plasma while we endorse paying for plasma; we therefore conclude in favour of a new Canadian regime of public sector plasma collection and compensation.